도서지역 신,재생복합 전력시스템 보급 타당성 분석 -3개 도서지역 분석결과 - 장하나; Ha Na Jang; 김수덕; Su Duk Kim (자원·환경경제연구, 2006)
A pre-feasibility test is done for renewable energy hybrid power systems at off~grid islands in which the current power supply is provided only by diesel generation. We apply Homer (Hybrid Optimization Model for Electric Renewables) which was developed by the National Renewable Energy Laboratory (NREL) for the analysis to identify the cost-minimizing combination of power generating facilities for the given load profiles. Chuja-Do, Geomun-Do and Youngsan-Do have been selected for our analysis considering the wind resources data of the Korea Institute of Energy Research (KIER). Information on wind speed, solar radiation and temperature is also used for the analysis. System component cost information from overseas market has been used due to the lack of domestic information. Site specific Load profile for electricity demand for those islands are reconstructed based on the partial survey results obtained form other sources. The LCOE of the least cost hybrid power systems for Chuja-Do, Geomun-Do and Youngsan-Do are $0.278/kWh, $0.234/kWh and $0.353/kWh, respectively Considering the fact that diesel generation is being subsidized at the price of $0.300/kWh by the government, first 2 cases are economically feasible for the introduction of renewable energy hybrid systems to those islands. But the third case of Youngsan-Do does not meet the criteria. The basic differences of these pre-feasibility test results are from the differences of the site specific renewable energy conditions, especially wind resources. In summary, promoting hybrid systems in the off-grid remote island should be based on the economic feasibility test results. Not all the off-grid islands are feasible for introducing this renewable energy hybrid system. 하이브리드 시스템의 최적 설계 및 운영을 위한 프로그램으로 해외의 여러 곳에서 활용중인 Homer를 사용하여 현재 디젤발전기를 전원으로 사용하고 있는 독립계통의 도서지역에 신 재생에너지원의 조합으로 구성된 하이브리드 시스템을 보급할 경우의 타당성 분석을 시도하였다. 에너지기술연구원의 풍속자료, 일사량, 온도자료 등을 근거로 추자도, 거문도, 그리고 영산도를 평가대상으로 선정하였다. 해당지역의 전력부하 자료는 부분적으로 실측된 자료를 바탕으로 재구성하였으며, 시스템 구성 발전기들의 비용 자료는 국내 관련 자료가 미비한 관제로 해외 시장의 자료를 이용하였다. 추자도, 거문도, 영산도의 평가결과가 각각 278원/kWh, 234원/kWh 그리고 353원/kWh으로 나타났다. 정부 보조금에 의한 디젤발전시스템의 발전단가가 300원/kWh($0.300/kWh)인 것을 고려한다면, 추자도와 거문도는 자체적으로 경제성을 확보하는 반면 영산도의 경우는 그렇지 못함을 알 수 있다. 이러한 결과 차이는 기본적으로 해당지역의 재생에너지 자원조건의 차이, 그 중에서도 특히 풍력자원의 차이에 기인하는 것으로 나타난다. 결론적으로 독립계통의 도서지역에 대한 신 재생복합전력시스템의 도입은 경제성 평가의 결과에 의거해야 하며 모든 도서지역이 이 조건을 충족시키는 것이 아님을 지적한다.